Analysis of Pulmonary Function between E-Cigarette Users and Non-Smokers Aged 20–30 Years in Jakarta - Digambiro, Reza Aditya; Parwanto, Edy; Tjahjadi, David; Ditriana, Ditriana (Jurnal Respirologi Indonesia, 2025)
Background: This study aimed to compare pulmonary function between e-cigarette users and non-smokers aged 20–30 years in Jakarta. Methods: A cross-sectional study was carried out between May 2023 and May 2024 at SMC Clinic Jakarta, Ibnusina Hospital Jakarta, and Naura Medika Clinic Depok. The sample consisted of 65 individuals who used e-cigarettes and 63 individuals who did not smoke. Spirometry was employed to evaluate pulmonary function by measuring forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and the FEV1/FVC ratio. The data were analyzed using independent t-tests using IBM SPSS software version 25.0. Results: The study revealed substantial disparities in pulmonary function between individuals who use e-cigarettes and those who do not smoke. Individuals who use e-cigarettes had significantly reduced FEV1 at 3.02±0.50 L and FVC at 4.00±0.47 L, in comparison to non-smokers (FEV1=3.51±0.57 L; FVC=4.57±0.50 L). E-cigarette users exhibited a considerably lower FEV1/FVC ratio (74.86±5.55) compared to non-smokers (79.29±5.11), suggesting a higher occurrence of obstructive airway diseases. Conclusion: Young adults aged 20-30 years in Jakarta who use e-cigarettes experience a decrease in pulmonary function. The results emphasize the possible respiratory hazards associated with the use of e-cigarettes and emphasize the necessity for greater awareness and regulatory actions to tackle these hazards.